تقييد صلح العمد في لبيبا دراسة تطبيقية في ضوء أحكام الشريعة الإسلامية: المقاصد، القواعد الفقهية: "Restricting Conciliation in Cases of Intentional Killing in Libya: An Applied Study in Light of Islamic Sharia: Objectives and Jurisprudential Principles - Elbalazi, Samira Hasan; Mohamed Razi, Nor Fahimah; Abdul Khalil, Shahidra (AL-HIKMAH: INTERNATIONAL JOURNAL OF ISLAMIC STUDIES AND HUMAN SCIENCES, 2025)
ملخص البحث تناولت الدراسة تحديد صلح العمد في المجتمع الليبي مدينة بنغازي والدوائر التابعة لها، لمعرفة تحقق العلة التي أبيح فيها الصلح على أكثر من الدية؛ بعد أن أخذت الدية في التصاعد ما يخشى عدم القدرة على أدائها ما يجعل البحث حولها أمر مهم لما يترتب عليها من مصالح للفرد والجماعة، استخدمت الباحثة المنهج الاستقرائي والمنهج التحليلي والمنهج المقارن للوصول إلى الحكم عن طريق تقييد المباح والاستعانة بالقواعد الفقهية ومبدأ سد الذرائع، أوضحت الدراسة أن جواز الصلح غير المحدد في مقدار الدية لا ينطبق على الواقع الليبي وفقًا لسندات الصلح، مما يرجّح تقييد المباح وفق الضرورة والمصلحة الطارئة، وتبيّن صحة الجمع بين أدلة عرض الدية ابتداء ثم الزيادة، وهو ما يدعم استحسان الحكم للضرورة، ويحقق مقاصد الشريعة، توصي الدراسة وضع قانون لتنظيم آلية دية العمد وتحديدها. ABSTRACT This study examines the practice of reconciliation in cases of intentional homicide (Ṣulḥ al-ʿAmad) within Libyan society, focusing on Benghazi and its surrounding districts. The research explores whether the justification for permitting reconciliation that exceeds the standard diyah (blood money) remains valid in today’s context, especially with the continuous rise in diyah amounts, which poses challenges to payment and raises significant social and legal concerns.To address this issue, the researcher applied inductive, analytical, and comparative approaches, drawing on juristic maxims and the principle of blocking the means (sadd al-dharāʾiʿ). The findings indicate that the unrestricted acceptance of reconciliation for any amount beyond the prescribed diyah does not align with current Libyan practice, as reflected in formal reconciliation agreements. Instead, the results support limiting permissibility in accordance with necessity and public interest. The study further shows that it is valid to begin with the diyah amount and then allow for additional sums when required, as this approach balances necessity with the higher objectives of Islamic law (maqāṣid al-sharīʿah). Such a framework ensures fairness, prevents harm, and upholds social stability.In conclusion, the study recommends enacting a legal framework to regulate reconciliation in intentional homicide cases by defining clear rules for the payment of diyah and its permissible adjustments. This would provide consistency, protect the rights of all parties, and enhance harmony within Libyan society.